Synaptic responses of cortical pyramidal neurons to light stimulation in the isolated turtle visual system - Kriegstein, AR (J Neurosci, 1987)
The resistance of the turtle brain to hypoxic injury permits a unique in vitro preparation in which the organization and function of visual cortex can be explored. Intracellular recordings from cortical pyramidal neurons revealed biphasic responses to flashes of light, consisting of an early phase (50–100 msec) of concurrent inhibitory and excitatory activation, followed by a longer, inhibitory phase (250–600 msec) composed of summated Cl- -dependent postsynaptic potentials mediated by GABA. This response sequence results from the coactivation of pyramidal and GABAergic non-pyramidal cells, followed by feed- forward and possibly feed-back pyramidal cell inhibition, and is partly dependent on differences in the membrane properties of pyramidal and non-pyramidal neurons.